Actualización de Balance Hídrico del Valle Virú - Cabrera Carlos, Jhon Jhonatan (2015)
This research work, describes the study of the update of the water balance surface and underground of the Valley Viru, freedom, also develops a model of the balance sheet in the software "WEAP", this will allow you to predict the future status of the components supply Vs demand of the water resource in the Valley, taking in this way a tool that lets you perform Water Management in the Valley. The data used have been mainly provided by the Special Project Chavimochic and Board of Users of irrigation in the basin of the Viru River. The study includes the analysis of water demand and total supply of the valley, efficiency of operation and application through traditional irrigation and new areas (Sector III and IV) of the valley Viru, recharge and discharge groundwater of the valley. The water balance Current (2014), indicates that the Valley Viru presents a total recharge of 160.49 hm3, a discharge total of 105.16 hm3, that is at the level of Valley is recharged with 55.33 HM3. At the start of the operation of the project for the exploitation of groundwater for the valley (56.9 hm3), we will have a recharge net of the Valley of 0.44 hm3, this estimate is the product of the calculation taking as flow supply 75% of persistence of the Rio Viru, without changing the supply delivered by the Special Project Chavimochic, in addition, the situation is valid when the demands do not vary significantly. The generation of the model through the Software WEAP, was calibrated with the demand and offers registered vs the demands and offers simulated by the program, the model shows a good degree of correlation, there was a validation of the data with supply delivered through the valley in the year 2014 including and not including the exploitation of groundwater. There was also the sensitivity analysis of the model, the parameters used was the pace of water use per year and values of connections of demand.